Student facilitator and explaining learning: Its use to increase student learning outcomes - Isa, Abd. Hamid; Mahmud, Yane Hardiyanti; Labodu, Delfiyanti Idris (Univeritas Papua, 2023)
This research aims to determine the improvement in student learning outcomes through the application of the student facilitator and explaining learning. The method used in this research is Classroom Action Research. The subjects are students in Class V.1 MI Muhammadiyah Unggulan Gorontalo City with a total of 28 students. The instruments in this research are teacher and student activity observation sheets, and learning outcomes tests. The research results showed that there was an increase in student learning outcomes in cycle 1 for the first meeting by 25%, 29% for the second meeting, and 36% for the third meeting. At the first meeting of cycle II the increase was 67% and 92% for the second meeting. This research concluded that overall there was an increase and the criteria for learning completeness were met. Using the student facilitator and explaining learning optimally can familiarize students with presenting their ideas to friends and have an impact on their learning outcomes.